Use of Rome II versus Rome III criteria for diagnosis of functional constipation in young children. Issue 1 (February 2014) - Osatakul, Seksit; Puetpaiboon, Areeruk
Abstract Background There has been no study to evaluate the use of the Rome III criteria for diagnosis of constipation in the unselected young pediatric population. The aim of this study was to evaluate and compare the use of the Rome II and Rome III criteria for diagnosis of constipation in a group of unselected young Thai children. Methods This cross‐sectional study was conducted in 3010 healthy children aged 4 months–5 years who attended a well‐baby clinic. Data concerning bowel habits and behavioral components of defecation of the children were obtained by interviewing the parents. Presence of a large fecal mass in the rectum of children with possible constipation was evaluated by abdominal palpation. Results Seventy‐one children (2.4%) were found to have constipation, based on at least one of the two sets of criteria, at the time of interview. The prevalence of constipation as defined according to the Rome II and Rome III criteria for functional constipation (FC) was 1.9% and 1.6%, respectively. The majority of constipated children (47.9%) met the diagnostic criteria of both the Rome II and Rome III for FC, followed by the Rome II criteria for FC alone (32.4%) and the Rome III criteria for FC alone (18.3%). Twenty‐one children (0.7%) whose parents reported defecation difficulties did not fulfill any diagnostic criteria for constipation. Conclusions The prevalence of FC in young Thai children is low. For unselected young children, the Rome II criteria for FC are still appropriate for diagnosis of FC.